Targeted Financial Sanctions of the United Nations: Status Quo in the Context of the Right to Fair Trial - Steponėnaitė, Viltė Kristina Kristina (Teisė, 2019)
[full article and abstract in Lithuanian; abstract in English] The article argues that while imposing targeted financial restrictive measures the United Nations shall comply with the requirements of the fundamental human rights, right to fair trial in particular. It is being argued respectively that, bearing in mind as argued the relevant guarantees of the right to fair trial, current review procedures for those subject to the targeted financial restrictive measures cannot be deemed to be in compliance with the requirements of the fair trial, therefore current situation on the United Nations level shall be deemed incompatible with the requirements of the fundamental human rights.